Estratificação vertical de quirópteros na Floresta Atlântica, Reserva Biológica Alto da Serra de Paranapiacaba - Santo André, SP - Paste, Rodrigo Fescina (2019)
By being actively embedded in the dynamics of forests, bats perform a range of ecosystem services, making the group key to ecological, agricultural and economic interests. Due to the structure of a forest influencing the vertical distribution of resources, the structure of a community of bats varies within the vertical structure and there are few studies that explore more than one forest stratum, as well as existing knowledge about bat ecology in the Atlantic forest, is underestimated. It is in this context that the objective is to characterize the community structure of bats in the use of vertical space in the Alto da Serra de Paranapiacaba Biological Reserve. By collecting bats by fog networks installed in the understory (3m), below-canopy(4-7m) and canopy (8-12m), we analyzed the frequency of species capture in each vertical stratum and related the frequency of catches in the different strata of each trophic guild registered with biotic variables ( weight and wingspan) and abiotic (humidity and temperature). For the 117 individuals of the 14 species captured, the results indicate that the community of bats in the region is regulated by the vertical structure, with the species Carollia perspicillata preferring exclusively the understory. Also the use of upper strata is associated with body size for frugivorous bats and enviroment temperature for insectivorous bats. This work highlights the need to explore the higher strata in inventories and wildlife monitoring programs.